Using livelihoods to support primary health care for South Sudanese refugees in Kiryandongo, Uganda - Ataria, Dominic Odwa; McKague, Kevin (African Journals Online (AJOL), 2019)
Introduction: Conflict in South Sudan has displaced 2.3 million people, of whom 789,098 (35%) have taken refuge in Uganda – a country that allows refugees to work, own property, start their own businesses and access public health services. In this context, refugees have identified livelihoods and primary health care as key priorities for their wellbeing. Objective: Building on previous research in South Sudan and Uganda, the objective of our current work is exploring how income-generating livelihood activities and other interventions can be used to support primary health care for South Sudanese refugees in Kiryandongo District, Uganda. Methods: We drew on existing secondary data and five scoping visits to the refugee settlements in Kiryandongo and northern Uganda to formulate our approach. Results: In Kiryandongo District, primary health care and livelihoods can best be supported by an integrated combination of 1) providing standardised training to local Village Health Teams (VHTs); 2) helping organise VHTs into village savings and loan association groups; and 3) supporting VHTs with training to establish sustainable income-generating activities. Conclusions: Integrated interventions that address income-generating activities for community health workers can meet the basic needs of front-line volunteer primary health care staff and better enable them to improve the health of their communities.